COVID-19 Awareness through Visual Communication: A Comparative Analysis on the Facebook Pages of NGOs and Media in Bangladesh - Biswas, Arnab; Ahsan, Ali; Hasan, Mahmudul (South Asian Journal of Social Sciences and Humanities, 2022)
This study aims to present a comparative analysis on the nature and characteristics of visual awareness messages disseminated through Facebook pages of NGOs and media at the very beginning of the COVID-19 outbreak in Bangladesh. A total number of 242 video and 116 image contents have been collected from three media and three non-governmental organizations and examined through their total received views and reactions. The findings show that the contents of media received more views and reactions than the contents of non-governmental organizations (NGO), whereas the NGO’s contents were more diverse than media contents. Among the awareness-building contents explainer video, infographic video and image, and videos with the presence of celebrity received higher views and reactions than others.